Estrogen replacement therapy and cardioprotection: mechanisms and controversies - Subbiah,M.T.R. (2002)
Epidemiological and case-controlled studies suggest that estrogen replacement therapy might be beneficial in terms of primary prevention of coronary heart disease (CHD). This beneficial effect of estrogens was initially considered to be due to the reduction of low density lipoproteins (LDL) and to increases in high density lipoproteins (HDL). Recent studies have shown that estrogens protect against oxidative stress and decrease LDL oxidation. Estrogens have direct effects on the arterial tissue and modulate vascular reactivity through nitric oxide and prostaglandin synthesis. While many of the effects of estrogen on vascular tissue are believed to be mediated by estrogen receptors alpha and ß, there is evidence for `immediate non-genomic' effects. The role of HDL in interacting with 17ß-estradiol including its esterification and transfer of esterified estrogens to LDL is beginning to be elucidated. Despite the suggested positive effects of estrogens, two recent placebo-controlled clinical trials in women with CHD did not detect any beneficial effects on overall coronary events with estrogen therapy. In fact, there was an increase in CHD events in some women. Mutations in thrombogenic genes (factor V Leiden, prothrombin mutation, etc.) in a subset of women may play a role in this unexpected finding. Thus, the cardioprotective effect of estrogens appears to be more complicated than originally thought and requires more research.